Introduction and studying of the species polymorphism in the almond genetic diversity preserved at Krymsk Experiment Breeding Station of VIR in the prebreeding stage - I. S. Chepinoga (Труды по прикладной ботанике, генетике и селекции)
Modern trends and ways of resuming and increasing the production of domestic almond kernels based on the development of cultivars that have advantages in adaptability, productivity, and kernel quality, and are distinguished for a quick payback are discussed. The results of VIR’s expeditions that collected almond species and varieties in Southern Russia, the Transcaucasus, and Central Asia are presented. Almonds introduced from foreign research institutions are also described.Analytical selection helped to identify complex sources of resistance to abiotic factors: ‘Victoria’ (k-42684), ‘Meteor’ (k-42683), ‘Dessertny’ (k-43550), Ai-Dere No.4 (k-42676), Ai-Dere No.5 (k-42677), Kolod 6 (k-42709), Podvoyny 205 (k-42678), ‘Tuono’ (k-49598), and Ferraduel × Tuono (k-43561). Promising source material is recommended for targeted development of new competitive almond cultivars for intensive horticulture, including sources of restrained growth type, compact crown, and earliness: Ferraduel × Tuono, ‘Monterey’(k-49538), elite 1-18-2 (k-42679), elite 2-40 (k-42680), and Kalmykov’s almond seedling 1-1 (k-42711); of productivity and almond kernel quality: Ferraduel × Tuono, ‘Monterey’, ‘Victoria’, ‘Meteor’, ‘Mindalny’ (k-42682), ‘Ferragness’ (k-42696), ‘Tuono’, ‘Karmeil’ (k-49540), elite 1-18-2, and Kalmykov’s almond seedling 1-1; of high oil content in kernels: elite 13-37 (k-42681); and of valuable fatty acid composition (according to the content of unsaturated fatty acids): cv. ‘Victoria’, elites 1-18-2 and 2-40, and Kolod 5 (k-42708).